Digital Marketing Strengthening CV. Kajeye Food Using Design Thinking Method - Nabila, Sinthok; Maheswari, Ardiella Sukma; Syindunata, Karina; Andini, Adelia Rahma; Ningsih, Yesi Mustika (Majapahit Journal of Islamic Finance and Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important and strategic role in the Indonesian economy and in employment absorption. One of the MSMEs located in Malang City, CV. Kajeye Food, operates in the souvenir and snack sector. CV. Kajeye Food is currently developing its digital marketing efforts. This study aims to design an appropriate digital marketing platform to increase sales. The design platform uses qualitative methods with the design thinking approach, consisting of five stages: empathizing, defining, ideating, prototyping, and testing. Benchmarking is also used as a supporting method in this study. As a result, several digital platforms were designed, including Instagram, TikTok, TikTok Shop, WhatsApp (specifically for sales), and Shopee. By utilizing these digital marketing platforms, CV. Kajeye Food is able to reach a wider range of consumers and increase its sales.